Hubungan Antara Pendidikan Karakter dengan Kecerdasan Sosial Siswa Kelas V SDN Gugus V Kecamatan Cakranegara Tahun Pelajaran 2018/2019 - Ni Made Dwi Trisnayani; Khairun Nisa; Abdul Kadir Jaelani (Indonesian Publication Center, 2020)
This research aims to identify the correlation between character education and social intelligence of fifth grade students of SDN Cluster V District Cakranegara academic year 2018/2019. The research design used is a quantitative approach to the type of correlational research. The population in this study were all fifth-grade students of SDN Cluster V Cakranegara subdistrict, amounting to 189 students. The sampling technique uses proportional random sampling technique so that a sample of 127 students is obtained. The data collection method used was a questionnaire. Data were analyzed by prerequisite test and hypothesis test. Hypothesis testing uses the product moment correlation formula. The results showed that: (1) Student character education in terms of aspects of tolerance, friendly/communicative, and social care as a whole gained an average score of 77 which was included in the sufficient category; (2) Social intelligence of students in terms of aspects of social sensitivity, social insight, and social communication as a whole obtained an average score of 74 included in both categories; (3) There is a significant relationship between character education and social intelligence of fifth grade students at SDN Cluster V Cakranegara subdistrict in the academic year 2018/2019 based on the results of hypothesis testing at N = 127 with a significance level of 5%, the results obtained are 0.740 (rtest)> 0.1743 (rtable), which is included in the level of relationship with a high category.